Keefektifan Pendidikan Matematika Realistik dan Means Ends Analysis terhadap Hasil Belajar Matematika Siswa - Indah Nurmalasari (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2016)
This study aims to determine differences in mathematics achievement between Realistic Mathematic Education (RME) class and Means Ends Analysis (MEA) class. A quasi-experimental method was adopted to obtain the answer to the research question. Sample of the study consisted of 65 fourth-grade students were selected by cluster random sampling from population that is all of the students in SDN Kembangan Selatan 01 Pagi. The sample consisted of by two groups, i.e. RME class that involved 32 students and MEA class that involved 33 students. The mathematics achievement data obtained by 6-item written test. Based on t-test analysis can be concluded that there is the difference between students' mathematics achievement by using RME and MEA. In this context, the research findings indicate that students’ mathematics achievement who received RME better than MEA. One of the factors supporting the finding is that the RME provides more opportunities for students to build meaningful learning through a process of reinventing the mathematical concepts.